A Bayesian approach to diagnosing covariance matrix shifts. (20th December 2019) - Wang, Binhui; Xu, Feng; Shu, Lianjie
Abstract: In addition to the quick detection of abnormal changes in a multivariate process, it is also critical to provide an accurate fault identification of responsible components following an out‐of‐control signal. In line with the work of Tan and Shi for diagnosing shifts in the mean vector, this paper develops a Bayesian approach for diagnosing shifts in the covariance matrix. The simulation comparisons favor the proposed approach. A real example is also presented to demonstrate the implementation of the proposed method.